A Rare Case Report: Primary Vulvar Adenocarcinoma of Mammary Gland Type - Dai X; Lei H; Jie R (International Journal of Women's Health)
Xiaomin Dai, Huan Lei, Ruixia Jie Department of Pathology, Zhejiang Hospital, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Ruixia Jie, Email 632331879@qq.comAbstract: Primary vulvar adenocarcinoma of mammary gland type (AMGT) is exceedingly rare and presents significant diagnostic challenges. We report the case of a 70-year-old female with a nodular vulvar lesion, confirmed as vulvar AMGT through comprehensive histological and immunohistochemical analysis. The tumor cells were positive for SOX10, TRPS1, and E-cadherin, and negative for ER, PR, and HER-2/neu, ruling out metastatic breast carcinoma. This case underscores the importance of specific markers like TRPS1 in accurately diagnosing rare vulvar malignancies and guiding effective treatment strategies. Further studies are needed to better understand the pathogenesis and clinical characteristics of vulvar AMGT.Keywords: vulva, adenocarcinoma, mammary gland type, differential diagnosis